Antidiabetic Effect Test of Ethanol Extract of Cep Cepan Leaf (Saurauia cauliflora Dc.) in Male Mouse (Mus musculus) Streptozotocin Induced - Pratiwi Rukmana Nasution; Nadroh Br Sitepu; Hilda S (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Cep-cepan leaves (Saurauia cauliflora DC.) have an antidiabetic effect due to the flavonoid compounds contained in them. As an antidiabetic so that it can be an alternative treatment for diabetes that is beneficial to improve quality of life, control diabetes and efficiency of medical costs. The approach employed in addressing antidiabetes involves the exploration of novel antidiabetic chemicals derived from medicinal plants. The Karo people in Medan, North Sumatra frequently utilize the cep-cepan plant (Saurauia Cauliflora DC.), a member of the Fagaceae family, as a medicinal remedy. The objective of this study is to investigate the impact and optimal dosage of cep cepan leaves produced by Saurauia cauliflora DC. The present study employs an experimental design utilizing a one-group pretest-posttest design. The study was carried out in Langkat Regency between May and December 2023. The population in this study was cep cepan as much as 5kg. The research sample was 3kg of cep cepan leaves taken by purposive sampling which had been dried. The dried cep cepan leaves were then blended to obtain a fine powder. Rats used in this study were rats that had blood glucose levels >200 mg/dl. Data analysis with the post hoc test used was the Mann-Whitney U Test, processing research data using SPSS software version 23. The results showed that the administration of Cep Cepan (Saurauia cauliflora DC.) leaf extract to mice (Mus musculus) at a dose of 200 mg/kg Body Weight/day for 12 days can reduce blood glucose levels in Balb/C male mice (Mus musculus) which is equivalent to glibenclamide. Keywords: Diabetes Mellittus, Mus Musculus ,Saurauia cauliflora Dc, Streptozotocin